Penalaran Atas Persamaan Akuntansi vs Persamaan Matematika - Sri Suryaningsum (Jurnal Akuntansi dan Keuangan, 2013)
This article is a critical review of the authors expressed of mathematical equations by Warsono et al (2009a, 2009b, 2009c) in Accounting Introduction to learning. This critical review discusses in detail that the accounting equation is not a mathematical equation, the accounting equation with the concept of unity of effort, GAAP (accounting principles generally acceptable), and articulation antarlaporan in accounting information. Learning objectives Introduction to Accounting course is not just skill alone. Introduction to Accounting course is designed with the goal of fully accounting me- mahamkan/mengenalkan not to menerampilkan learners to simply analyze the transaction and journaling. Accounting implications in the learning process will be described in detail the cause (why) reasoning errors accounting equation and how its impact on the process of creating the phenomenon of insight and attitudes towards accounting.